Hepatic carcinosarcoma: a rare and aggressive case with unusual molecular signature! - Almahari, Sayed Ali; Al-Ani, Maryam; Zaitoun, Abed M; Gordon, Gregory; Ibrahim, Samiya; Arora, Arvind; Baraka, Bahaaeldin (Frontiers in Oncology, 2026)
BackgroundPrimary hepatic carcinosarcoma is a rare, aggressive tumour with both carcinomatous and sarcomatous components. Limited documented cases hinder comprehensive understanding, making diagnosis, treatment, and management particularly challenging for clinicians.CaseA 62-year-old female, with prior cervical squamous cell carcinoma 7 years ago, underwent right hemihepatectomy, cholecystectomy, and diaphragmatic resection in 2025. Grossly, a 180 mm white hepatic tumour with a large cystic cavity was seen adherent to the diaphragm, extending to the resection margin (R2), while the hepatic resection margin was clear (R0). Histology confirmed hepatic carcinosarcoma (pT4), comprising cholangiocarcinoma (CK7, BerEP4+), hepatocellular carcinoma (Glypican-3+), and squamous carcinoma (p63, p40+). Sarcomatous areas included rhabdomyosarcomatous (Desmin, Myogenin, MyoD1+), leiomyosarcomatous (SMA+), and chondrosarcomatous (S100+) differentiation. PLAP and CD117 positivity suggested germ cell-like features. There is no distinct separation between the carcinomatous and sarcomatous components. Molecular profiling revealed a KIAA1549::BRAF fusion alongside oncogenic variants: TERT c.-124C>T (VAF 0.60) and TP53 c.811G>A p. (Glu271Lys) (VAF 0.90). Targeted panel sequencing showed no other actionable mutations. MSI readout was 2.5%, confirming microsatellite stability (MSS).OutcomeMultidisciplinary review at tertiary centres confirmed the rarity and grave outlook. The patient developed early recurrence with thoraco-abdominal deposits, venous thromboembolism, and pleural effusion. Paclitaxel–carboplatin chemotherapy was commenced with dose modifications for hepatotoxicity, complicated by infusion reactions, mild neuropathy, and mucositis.ConclusionThis case underlines the extreme morphological and molecular heterogeneity of hepatic carcinosarcomas, the rapid progression despite surgery, and the limited systemic treatment options available for such rare tumours.